Influence of Organizational Commitment, Work Environment, and Work Motivation as Intervening Variables on Job Satisfaction of Employees Directorate General of Foreign Trade, Ministry of Trade - Priyo Tri Atmojo; M. Ali Iqbal; Parwoto Parwoto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the factors that influence the job satisfaction of employees of the Directorate General of Foreign Trade, Ministry of Trade. The population of this study was all employees of the Directorate General of Foreign Trade of the Ministry of Trade with a total sample of 162 employees with an observation period of 2022. The endogenous variables used were work motivation and job satisfaction, while the exogenous variables used were organizational commitment and work environment. The data analysis method used Structural Equation Model-Partial Least Square (SEM-PLS). The results showed that organizational commitment and work environment had a positive and significant effect on work motivation; organizational commitment and work environment have no significant effect on job satisfaction; work motivation has a positive and significant effect on job satisfaction; work motivation can mediate the effect of organizational commitment and work environment on job satisfaction.